Preparation of Graphene-Like Porous Carbons With Enhanced Thermal Conductivities From Lignin Nano-particles by Combining Hydrothermal Carbonization and Pyrolysis - Dong, Huiling; Li, Min; Jin, Yongcan; Wu, Yan; Huang, Caoxing; Yang, Jinlai (Frontiers in Energy Research, 2020)
Lignin nano-particles (LNPs) exhibit properties that distinguish them with regard to production of lignin-based materials. However, little research has been performed to investigate whether porous carbons produced from LNPs exhibit performance superior to those derived from untreated lignin. In this study, lignin was fabricated into lignin nano-particles (LNP) and used to prepare high-performance porous carbons with enhanced thermal conductivities comparing to that of the carbons from neat lignin. Two different preparation protocols were employed: direct pyrolysis and hydrothermal carbonization followed by pyrolysis. Carbons obtained from 100 nm–300 nm LNPs possessed more graphene-like structures than carbons from unaltered lignin. In addition, carbons prepared using a combination of hydrothermal carbonization and pyrolysis exhibited higher specific surface areas (108.81 m2/g–220.75 m2/g) and total pore volumes (0.098 cm3/g–0.166 cm3/g) than those prepared via direct pyrolysis. In addition, LNP-derived carbons exhibited superior thermal conductivities (0.45 W/mK) and thermal conductivity rates (0.51 oC/s). This work provides the useful finding that superior graphene-like porous carbons can be produced by transforming lignin into LNP and then hydrothermally carbonizing the resulting material prior to pyrolysis.